2021
DOI: 10.1038/s41598-021-89293-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of regional differences on agricultural water resource utilization efficiency using super-efficiency SBM model

Abstract: This study evaluated the water resource utilization efficiency and resource consumption for planting, forestry, animal husbandry, and fishery in various regions of China. Using the super-efficiency Slacks-Based Measure (SBM) analysis method, the main agricultural pollution emissions (Chemical Oxygen Demand, ammonia nitrogen, and agricultural carbon emissions) were proposed as environmental constraints for the first time. The threshold regression model was used to measure the impact of agricultural water use ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…WUE of cities is not only related to their economic strength, but also connected to the water management level and the local physical endowment (Zhu and Tang, 2020). In general, the WUE is significantly lower in the agriculture sector than the industry and service sectors (Geng et al, 2019;Huang et al, 2021), higher in water-deficient or vulnerable regions than in water-rich regions (Guo et al, 2019), and lower in cities and towns than in rural areas (Hai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…WUE of cities is not only related to their economic strength, but also connected to the water management level and the local physical endowment (Zhu and Tang, 2020). In general, the WUE is significantly lower in the agriculture sector than the industry and service sectors (Geng et al, 2019;Huang et al, 2021), higher in water-deficient or vulnerable regions than in water-rich regions (Guo et al, 2019), and lower in cities and towns than in rural areas (Hai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional DEA model omits the internal structure of the model and cannot decompose and measure the total efficiency. Therefore, we use a two-stage dynamic SBM model to decompose and carry the research process more robustly as suggested by Huang et al (2021b). Second, the static model based on cross-sectional data cannot see the dynamic efficiency changes between DMUs.…”
Section: Methodsmentioning
confidence: 99%
“…The SE-SBM model considers expected and unexpected output, so it is widely used in efficiency measurement in various fields. Huang et al [22] calculated the utilization efficiency of agricultural water resources through the super efficiency SBM model and provided reasonable suggestions for utilizing regional water resources. Long et al [23] proposed an SBM-DEA model with unexpected output efficiency to measure urban ecological sustainable development.…”
Section: Plos Onementioning
confidence: 99%